Pengembangan Sistem Pelayanan Kesehatan Poli Spesialis berbasis Web (Studi Kasus : Poliklinik RS Elizabeth Situbondo) - Sheila Aprilia Putri; Denny Sagita Rusdianto; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
As one of the services at Elizabeth Situbondo Hospital, poly specialists provide a medical service in the form of medical measures related to medical examinations, treatment and outpatient consultations for patients, which will be reported in a document in the form of medical records. Medical records are files containing records of patient identification, examination, treatment, actions and other services to patients in health care facilities. Each unit in poly RSE must be able to work appropriately in knowing the data of poly patients, obtaining reports of patient medical data according to what is needed and what certain parties want according to their role in the RSE poly unit. The implementation of medical record activities related to procedures imposed by RSE there are constraints on difficulties in data exchange activities or various patient health information, because the patient's medical record data is only stored locally in the place where the patient undergoes examination and medical treatment and between places does not allow direct exchange of data.. Based on this, this research aims to build a system that can help hospitals in the management of poly health services. As well as the large number of people who receive treatment makes the importance of managing health information, thereby helping the hospital in facilitating information sharing and data exchange between medical staff. This system was created using Waterfall development method. In the process of engineering needs, there are 75 functional needs and 1 non functional needs. The PHP, HTML, Javascript and CodeIgniter programming languages are implemented in system development. In the test, 100% valid results were obtained for all system needs. Non-functional needs testing was tested using the SUS method which resulted in a final value of 61 so that it belonged to the category